Lithium ion battery and application thereof
By using nickel-cobalt lithium manganate material and doped lithium iron phosphate material in the positive electrode active material of the lithium-ion battery, a structure in which the second active material coats the first active material is formed, and the capacity attenuation problem caused by the electrochemical reaction of the positive and negative electrode interface during the charging and discharging of the lithium-ion battery is solved, and the battery cycle life and storage performance are improved.
Patent Information
- Application Number
- CN202311373324.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-20
- Publication Date
- 2025-04-22
AI Technical Summary
During the charging and discharging process of lithium-ion batteries, electrochemical reactions occur at the interface of positive and negative electrodes, resulting in lithium-ion loss, battery capacity attenuation, performance degradation, and service life shortened.
A lithium-ion battery is used, and its positive electrode active material consists of a first active substance (such as a nickel-cobalt lithium manganate material) and a second active substance (such as a doped lithium iron phosphate material). The second active substance is coated on the first active substance, and its particle size ratio and doping ratio are controlled to prevent side reactions of the positive electrode active material and the electrolyte.
It effectively extends the cycle life and storage performance of lithium-ion batteries, improves the economic benefits of the battery, ensures that the battery capacity retention rate is greater than 90%, and the number of cycles is greater than 1,900.
Smart Images

Figure CN119864481A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a lithium ion battery and applications thereof. Background Art
[0002] Rechargeable secondary lithium batteries are widely used as energy sources in wireless mobile devices, and secondary lithium batteries have been widely used as power sources for electric vehicles and hybrid electric vehicles, which can effectively solve the air pollution problem caused by gasoline and diesel engines using petroleum.
[0003] During the charge and discharge process of secondary lithium batteries, electrochemical reactions occur at the interface between the positive and negative electrodes, accompanied by side reactions. As the number of charge and discharge cycles increases, lithium ions will be lost to a certain extent, resulting in a decrease in battery capacity and performance, which greatly reduces the service life of secondary lithium batteries. Summary of the invention
[0004] The present invention provides a lithium ion battery and application thereof, which can effectively prevent the positive electrode active material of the lithium ion battery from having a side reaction with an electrolyte, thereby improving the cycle life of the lithium ion battery.
[0005] To solve the above technical problems, the present invention is achieved through the following technical solutions:
[0006] The present invention provides a lithium ion battery, comprising a positive electrode sheet, a negative electrode sheet and a separator located between the positive electrode sheet and the negative electrode sheet, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode active material located on at least one surface thereof, and the negative electrode sheet comprises a negative electrode current collector and a negative electrode active material located on at least one surface thereof, wherein the positive electrode active material comprises at least:
[0007] a first active substance; and
[0008] a second active substance, wherein the second active substance is coated on the first active substance;
[0009] The area of the second active material covering the first active material accounts for 5% to 20% of the area of the first active material, and the average particle size D of the first active material is 50 The average particle size D of the second active material 50 The ratio ranges from (3:1) to (15:1).
[0010] In one embodiment of the present invention, the mass proportion a of the second active material in the first active material and the second active material and the capacity attenuation coefficient y satisfy the relationship:
[0011] y=-4×10 -5x+m1, where 5%≤a≤10%, 0.9646≤m1≤0.9846;
[0012] y=-3×10 -5 x+m2, where 10%<a≤20%, 0.9718≤m2≤0.9918;
[0013] y=-3×10 -5 x+m3, where 20%<a≤30%, 0.9787≤m3≤0.9987;
[0014] Wherein, x is the number of cycles, m1, m2 and m3 are the initial capacity attenuation coefficients of the lithium-ion battery, the capacity attenuation coefficient y is the ratio of the discharge capacity of the xth cycle to the first discharge capacity, and 50≤x≤2000.
[0015] In one embodiment of the present invention, the mass ratio of the second active material doped with the first active material is 5% to 25%.
[0016] In one embodiment of the present invention, the minimum particle size D of the first active material is min1 With the maximum particle size D max1 The ratio ranges from (1:3) to (1:8).
[0017] In one embodiment of the present invention, the minimum particle size D of the second active material is min2 With the maximum particle size D max2 The ratio ranges from (1:2) to (1:10).
[0018] In one embodiment of the present invention, the first active material at least comprises a nickel cobalt manganese oxide material, and the general formula of the nickel cobalt manganese oxide material is LiNi m Co n Mn 1-m-n O2, where 0.1≤m≤0.9, 0<n≤0.3.
[0019] In one embodiment of the present invention, the second active material at least includes a doped lithium iron phosphate material, the general formula of the lithium iron phosphate material is LiFeMPO4, wherein the element M is at least one of Mn, Ti, Zr, Al, Sn, Zn, Mg, Cu, In, Ga or Ta.
[0020] In one embodiment of the present invention, the recovery capacity of the lithium-ion battery within 45 days is greater than 100%.
[0021] In one embodiment of the present invention, the surface density of the positive electrode sheet is 1.4 to 3 times that of the negative electrode sheet.
[0022] The present invention also provides an electrochemical device, comprising the above-mentioned lithium-ion battery.
[0023] In summary, the present invention proposes a lithium-ion battery and its application, selects the particle size ratio of the first active material and the second active material, selects the first active material and the second active material of different particle sizes and mixes them in different proportions to prepare the positive electrode active material of the lithium battery, improves the compaction density and filling density of the pole piece, thereby improving the capacity of the lithium-ion battery, improving the cycle stability and storage performance of the lithium-ion battery, and improving the economic benefits of the lithium-ion battery. At the same time, the formation of a structure in which the second active material covers the first active material can effectively control the side reactions between the positive electrode active material and the electrolyte in the lithium-ion battery, thereby extending the service life of the lithium-ion battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0025] Figure 1 This is a scanning electron microscope image of the second active material coating the first active material in one embodiment of the present invention.
[0026] Figure 2 Graphs showing the cycle trends of lithium-ion batteries in different embodiments and comparative examples of the present invention.
[0027] Figure 3 Schematic diagram of storage performance of lithium-ion batteries in different embodiments and comparative examples of the present invention DETAILED DESCRIPTION
[0028] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.
[0029] It should be understood that the present invention can be implemented in different forms and should not be interpreted as limited to the embodiments set forth herein. On the contrary, these embodiments are provided to make the disclosure thorough and complete and to fully convey the scope of the present invention to those skilled in the art.
[0030] The technical solution of the present invention is further described in detail below in conjunction with several embodiments and drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0031] The nickel-cobalt-lithium manganese oxide ternary material used in lithium-ion batteries has the advantages of high energy density, long cycle life at low cut-off voltage, ideal crystal structure, low self-discharge and no memory effect. Lithium iron phosphate material has the advantages of high electrochemical capacity, excellent normal and high temperature cycle performance, excellent safety performance, low cost and environmental friendliness. The composite material of the two uses the synergistic effect between the two components to give full play to the advantages of the two materials to meet the growing demand for high-performance lithium-ion batteries. It can be widely used in portable electronic products such as mobile phones, tablet computers, laptops and digital cameras, as well as in transportation tools such as electric bicycles and electric vehicles. The present invention proposes a lithium-ion battery and its application, which can be used in various electronic products and electric vehicle fields.
[0032] See also Figure 1 As shown, the present invention proposes a lithium-ion battery, which is, for example, a secondary lithium-ion battery, and the lithium-ion battery includes a positive electrode sheet, a negative electrode sheet and a separator, wherein the separator is disposed between the positive electrode sheet and the negative electrode sheet to separate the positive electrode sheet from the negative electrode sheet. The positive electrode sheet, for example, includes a positive electrode current collector and a positive electrode coating located on at least one surface of the positive electrode current collector, wherein the material of the positive electrode current collector is, for example, aluminum foil, and the positive electrode coating, for example, includes at least a positive electrode active material. The negative electrode sheet, for example, includes a negative electrode current collector and a negative electrode coating located on at least one surface of the negative electrode current collector, wherein the material of the negative electrode current collector is, for example, copper foil. In this embodiment, the surface density of the positive electrode sheet is, for example, 0.01 g / cm 2 ~0.02g / cm 2 The negative electrode surface density is, for example, 0.007 g / cm 2 ~0.013g / cm 2 , and the surface density of the positive electrode sheet is, for example, 1.4 to 3 times the surface density of the negative electrode sheet, so as to ensure the fast charging performance and cycle performance of the lithium-ion battery. The positive electrode sheet, the separator and the negative electrode sheet are, for example, stacked in sequence, and the positive electrode sheet, the separator and the negative electrode sheet are immersed in an electrolyte to obtain a lithium-ion battery.
[0033] See also Figure 1 As shown, in one embodiment of the present invention, the positive electrode active material includes at least a first active material and a second active material. The first active material accounts for 70wt% to 95wt% of the total mass of the positive electrode coating, and the first active material is, for example, a nickel cobalt manganese oxide material. The general formula of the nickel cobalt manganese oxide material is, for example, LiNi m Con Mn 1-m-n O2, wherein 0.1≤m≤0.9, 0<n≤0.3. In this embodiment, the first active material comprises, for example, nickel cobalt manganese oxide materials of different particle sizes, and the first active material has a minimum particle size D min1 With the maximum particle size D max1 The ratio ranges from (1:3) to (1:8), and the particle size range of the first active material is, for example, 1.5 μm to 7.0 μm. The present invention does not limit the content of the first active material with different particle sizes, for example, it can be set according to other requirements.
[0034] See also Figure 1 As shown, in one embodiment of the present invention, the proportion of the second active material to the total mass of the positive electrode coating is, for example, 30wt% to 50wt%, and the second active material is, for example, at least a doped lithium iron phosphate material. The general formula of the lithium iron phosphate material is, for example, LiFeMPO4, wherein the element M is at least one of Mn, Ti, Zr, Al, Sn, Zn, Mg, Cu, In, Ga or Ta. In this embodiment, the second active material also includes, for example, lithium iron phosphate materials of different particle sizes, and the minimum particle size D of the second active material is min1 With the maximum particle size D max1 The ratio ranges from (1:2) to (1:10), and the particle size range of the second active material is, for example, 0.3 μm to 4 μm. The present invention does not limit the content of the second active material with different particle sizes, for example, it can be set according to other requirements.
[0035] See also Figure 1 As shown, in one embodiment of the present invention, the particle size of the second active material is smaller than the particle size of the first active material, and the average particle size D of the first active material is 50 The average particle size D of the second active material 50 The range of the ratio is, for example, (3:1) to (15:1). The second active material is doped in the first active material to form a structure in which the second active material is coated on the first active material. In this embodiment, the mass ratio of the second active material doped with the first active material is, for example, 5% to 25%, and the area of the second active material coating the first active material accounts for 5% to 20% of the area of the first active material. And the mass proportion a of the second active material in the first active material and the second active material and the capacity attenuation coefficient y satisfy the following relationship.
[0036] y=-4×10 -5 x+m1, where 5%≤a≤10%, 0.9646≤m1≤0.9846;
[0037] y=-3×10 -5x+m2, where 10%<a≤20%, 0.9718≤m2≤0.9918;
[0038] y=-3×10 -5 x+m3, where 20%<a≤30%, 0.9787≤m3≤0.9987;
[0039] Wherein, x is the number of cycles, m1, m2 and m3 are the initial capacity attenuation coefficients of the lithium-ion battery, the capacity attenuation coefficient y is the ratio of the discharge capacity of the xth cycle to the first discharge capacity, and 50≤x≤2000. The first active material and the second active material of different particle sizes are doped and coated in different proportions. By setting the particle size ratio of the first active material and the second active material, as well as the doping ratio of the two, the second active material with a small particle size is coated on the surface of the first active material with a large particle size, thereby preventing the occurrence of side reactions between the lithium nickel cobalt manganese oxide material and the electrolyte, thereby extending the service life of the battery cell and improving the economic benefits of the lithium-ion battery. At the same time, the particles of the two positive electrode active materials are better filled and fused together, which increases the compaction density and filling density of the pole piece, thereby increasing the capacity of the lithium-ion battery, and improving the dynamic performance and cycle life of the battery.
[0040] See also Figure 1 As shown, in one embodiment of the present invention, the positive electrode coating also includes substances such as a positive electrode conductive agent and a positive electrode binder. Among them, the conductive agent is selected from any one or more of conductive carbon black (Super P, SP), acetylene black, carbon nanotube (CarbonNanotube, CNT) and graphene, and the proportion of the conductive agent to the total mass of the positive electrode coating is, for example, 0.2wt% to 5wt%. The positive electrode binder is selected from one or more of oily binders such as polyvinylidene fluoride (Polyvinylidene Fluoride, PVDF), and the proportion of the positive electrode binder to the total mass of the positive electrode coating is, for example, 0.2wt% to 5wt%. The material of the positive electrode coating is dissolved in a positive electrode solvent to form a positive electrode slurry, which is then coated on a positive electrode current collector. The positive electrode solvent is selected from a mixture of one or more solvents such as N-methylpyrrolidone (N-Methyl-2-pyrrolidone, NMP), dimethylformamide (DiMethyl Formamide, DMF), and ethylene glycol dimethyl ether (Ethylene Glycol Dimethyl Ether, EGDME).
[0041] See also Figure 1As shown, in one embodiment of the present invention, the negative electrode coating includes a negative electrode active material, a negative electrode conductive agent, a negative electrode binder and a thickener. Among them, the negative electrode active material is selected from carbon-based negative electrode active materials such as crystalline carbon, amorphous carbon or carbon composite materials, or is a mixture of one or more graphite-based negative electrode active materials such as natural graphite and artificial graphite. The conductive agent is selected from any one or more of conductive carbon black (Super P, SP), acetylene black, carbon nanotubes (Carbon Nanotube, CNT) and graphene. The negative electrode binder is selected from any one or more of aqueous binders such as styrene butadiene rubber (Polymerized StyreneButadiene Rubber, SBR). The thickener is selected from one or more of carboxymethyl cellulose (Sodium Carboxymethyl Cellulose, CMC), carboxymethyl cellulose sodium (Carboxymethylcellulose sodium, CMC-Na) or sodium alginate (Sodium Alginate). The material of the negative electrode coating is dissolved in a negative electrode solvent to form a negative electrode slurry, which is coated on the negative electrode current collector. The negative electrode solvent is selected from a mixture of one or more aqueous solvents such as deionized water. The present invention does not limit the content of each component in the negative electrode coating, which can be set according to actual production conditions.
[0042] The present invention also provides a method for preparing a lithium ion battery. The lithium ion battery is obtained through the preparation method of steps S11 to S14.
[0043] Step S11: Mix the positive electrode active material, binder and conductive agent according to a set weight ratio, add them to the positive electrode solvent, and stir them under certain conditions until they are uniform to obtain positive electrode slurry. The positive electrode slurry is evenly coated on the positive electrode current collector, and then dried, cold pressed and cut to obtain positive electrode sheets.
[0044] Step S12: Mix the negative electrode active material, conductive agent, thickener, and binder according to a set mass ratio, add them to the negative electrode solvent, and stir them under certain conditions to obtain negative electrode slurry. The negative electrode slurry is evenly coated on the negative electrode current collector, and then dried, cold pressed, and cut to obtain a negative electrode sheet.
[0045] Step S13, mixing the organic solvents according to a proportion, adding lithium salt, additives and other ingredients, mixing evenly, and obtaining an electrolyte.
[0046] Step S14, stacking the separator and the positive electrode sheet and the negative electrode sheet prepared in steps S11 to S12, then wrapping them with aluminum plastic film, injecting the electrolyte prepared in step S13 after drying, and obtaining a lithium-ion battery through packaging, standing and formation processes.
[0047] In one embodiment of the present invention, in step S11, the positive electrode current collector can be selected from aluminum foil, etc., and the thickness of the positive electrode current collector is, for example, 10μm to 15μm. In this embodiment, the positive electrode active material is, for example, a second active material coating a first active material, the binder is, for example, polyvinylidene fluoride, the conductive agent is, for example, Super P, and the positive electrode current collector is, for example, 12μm aluminum foil. Specifically, the first active material, Super P and polyvinylidene fluoride coated with the second active material are mixed in a mass ratio of, for example, 97:1.5:1.5, and then N-methylpyrrolidone is added, and stirred until stable and uniform under the action of a vacuum mixer to obtain a positive electrode slurry, and the positive electrode slurry is coated on the aluminum foil. After the aluminum foil is dried at room temperature, it is transferred to a blast oven at 100℃-120℃ and dried for 0.5h-1h, and then the positive electrode sheet is obtained through cold pressing and slitting.
[0048] In one embodiment of the present invention, in step S12, the negative electrode current collector can be selected from copper foil, etc., and the thickness of the negative electrode current collector is, for example, 8μm to 12μm. In this embodiment, the binder is selected from styrene-butadiene rubber, the thickener is selected from carboxymethyl cellulose, the conductive agent is selected from acetylene black, and the positive electrode current collector is, for example, 10μm copper foil. Specifically, the negative electrode active material, acetylene black, carboxymethyl cellulose and styrene-butadiene rubber are mixed in a mass ratio of 96.4:1:1.2:1.4, deionized water is added, and the negative electrode slurry is obtained under the action of a vacuum mixer. The negative electrode slurry is evenly coated on the negative electrode current collector copper foil, the copper foil is placed in a blast drying oven, and dried at 120°C for 10 minutes, and the dried electrode sheet is rolled and cut to prepare the negative electrode sheet.
[0049] In one embodiment of the present invention, in step S13, the lithium salt is selected from any one or more of lithium hexafluorophosphate (LiPF6), lithium difluorophosphate (LiPO2F2), lithium bis(fluorosulfonyl)imide (LiFSi), lithium tetrafluoroborate (LiBF4), lithium difluoro(oxalato)borate (1-), LiDFOB or lithium bis(oxalate)borate (LiBOB). In this embodiment, the lithium salt is selected from LiPF6. The organic solvent is selected from any one or more of ethylene carbonate (EC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC) or polycarbonate (PC). In this embodiment, the organic solvent is, for example, a mixed solution of EC, EMC, and DEC, and the weight ratio of EC, EMC, and DEC is, for example, 1:1:1.
[0050] In one embodiment of the present invention, in step S14, the diaphragm 300 is, for example, selected from a polyethylene film (Polyethylene, PE) or a polypropylene film (Polypropylene, PP). The thickness of the diaphragm 300 is, for example, 5μm to 18μm, the air permeability is, for example, 180s / 100m to 380s / 100mL, and the porosity is, for example, 30% to 50%. In this embodiment, the diaphragm is, for example, a composite diaphragm material of PP / PE / PP, and the thickness of the diaphragm is, for example, 15μm. The positive and negative electrode sheets obtained in steps S11 to S12 are stacked in the order of positive electrode sheet, diaphragm, and negative electrode sheet, wrapped with aluminum-plastic film, transferred to a vacuum oven at 100°C to 130°C for drying, and sealed after injecting the electrolyte obtained in step S13, and finally a soft-pack battery with a capacity of 1Ah, i.e., a lithium-ion battery, is prepared.
[0051] The energy storage performance and cycle performance of the lithium ion battery obtained by the present invention are tested.
[0052] To test the cycle life of a lithium-ion battery, for example, at room temperature, charge to 4.4V at a constant current of 0.5C, and then cut off at a constant voltage of 0.05C, and let stand for 10 minutes. Discharge to 2.8V at a constant current of 1C, and let stand for 30 minutes. Record the capacity value and compare it with the initial discharge capacity to obtain the cycle life of the battery.
[0053] To test the storage performance of a lithium-ion battery, the battery is charged to 4.4V at a constant current of, for example, 0.5C, and then cut off at a constant voltage of 0.05C, and then stored in a constant temperature box at, for example, 60°C. The battery is taken out every 15 days, and charged and discharged once at, for example, 25°C, and then discharged to 2.8V at a constant current of, for example, 0.33C, and the capacity value is recorded and compared with the initial discharge capacity to obtain the storage performance of the battery.
[0054] The present invention also provides an electrochemical device, which includes the above-mentioned lithium-ion battery. Since the lithium-ion battery adopts all the above-mentioned technical solutions for the positive electrode active material, it at least has all the beneficial effects brought by the above-mentioned technical solutions for the positive electrode active material, which will not be described one by one here. Among them, the electrochemical device includes, for example, at least a battery module, a battery pack, an electric vehicle, an electric ship or an electric aircraft.
[0055] Hereinafter, the present invention will be explained in more detail by citing examples, which should not be construed as limiting. Appropriate modifications may be made within the scope consistent with the gist of the present invention, all of which fall within the technical scope of the present invention.
[0056] Example 1
[0057] Preparation of positive electrode active material: The average particle size D 50 The minimum particle size is 3.8 μm and D min1 The maximum particle size is 1.8 μm. max1 The first active material nickel cobalt manganese oxide material has an average particle size of 7.0 μm and an average particle size of D 50 The minimum particle size is 1.09 μm and D min1 The maximum particle size is 0.39 μm and D max1 The second active material is mixed with a lithium iron phosphate material with a diameter of 3.69 μm to form a lithium ion battery positive electrode active material in which the mass ratio of the second active material to the first active material is 5:95.
[0058] Preparation of positive electrode sheet: The above positive electrode active material, conductive agent Super P and binder polyvinylidene fluoride are mixed at a mass ratio of 97:1.5:1.5, and N-methylpyrrolidone is added to obtain positive electrode slurry under the action of a vacuum mixer. The positive electrode slurry is coated on aluminum foil, and the aluminum foil coated with the positive electrode slurry is dried at room temperature and transferred to a blast oven at 100℃-120℃ for drying for 0.5h-1h, and then the positive electrode sheet is obtained through cold pressing and slitting.
[0059] Preparation of negative electrode sheet: negative electrode active material, acetylene black, carboxymethyl cellulose and styrene butadiene rubber are mixed in a mass ratio of 96.4:1:1.2:1.4, deionized water is added, and negative electrode slurry is obtained under the action of a vacuum mixer. The negative electrode slurry is evenly coated on the negative electrode current collector copper foil, and the copper foil coated with the negative electrode slurry is placed in a blast drying oven and dried at 120°C for 10 minutes, and then the negative electrode sheet is obtained through cold pressing and slitting.
[0060] Preparation of electrolyte: Ethylene carbonate, ethyl methyl carbonate and diethyl carbonate are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L.
[0061] Preparation of lithium-ion battery: A porous membrane of PP / PE / PP with a thickness of 15um is selected as the separator, and the above-mentioned positive electrode sheet, separator and negative electrode sheet are stacked in sequence, and the stack is wrapped with aluminum-plastic film, and sealed after injecting electrolyte. After the formation and aging processes, a soft-pack battery with a capacity of 1Ah, i.e., a lithium-ion battery, is finally prepared.
[0062] Example 2
[0063] Preparation of positive electrode active material: The average particle size D 50 The minimum particle size is 3.8 μm. min1 The maximum particle size is 1.8 μm. max1 The first active material nickel cobalt manganese oxide material has an average particle size of 7.0 μm and an average particle size of D 50 The minimum particle size is 1.09 μm and D min1 The maximum particle size is 0.39 μm and D max1 The second active material is mixed with a lithium iron phosphate material with a diameter of 3.69 μm to form a lithium ion battery positive electrode active material in which the mass ratio of the second active material to the first active material is 10:90.
[0064] The other operations are the same as those in Example 1.
[0065] Example 3
[0066] Preparation of positive electrode active material: The average particle size D 50The minimum particle size is 3.8 μm. min1 The maximum particle size is 1.8 μm. max1 The first active material nickel cobalt manganese oxide material has an average particle size of 7.0 μm and an average particle size of D 50 The minimum particle size is 1.09 μm and D min1 The maximum particle size is 0.39 μm and D max1 The second active material is mixed with a lithium iron phosphate material with a diameter of 3.69 μm to form a lithium ion battery positive electrode active material in which the mass ratio of the second active material to the first active material is 20:80.
[0067] The other operations are the same as those in Example 1.
[0068] Example 4
[0069] Preparation of positive electrode active material: The average particle size D 50 The minimum particle size is 5.2 μm. min1 The maximum particle size is 1.8 μm. max1 The first active material nickel cobalt manganese oxide material has an average particle size of 7.0 μm and an average particle size of D 50 The minimum particle size is 1.2 μm. min1 The maximum particle size is 0.82 μm. max1 The second active material is mixed with a lithium iron phosphate material with a diameter of 3.69 μm to form a lithium ion battery positive electrode active material in which the mass ratio of the second active material to the first active material is 5:95.
[0070] The other operations are the same as those in Example 1.
[0071] Example 5
[0072] Preparation of positive electrode active material: The average particle size D 50 The minimum particle size is 13.1 μm. min1 The maximum particle size is 1.8 μm. max1 The first active material nickel cobalt manganese oxide material has an average particle size of 7.0 μm and an average particle size of D 50 The minimum particle size is 1.2 μm. min1 The maximum particle size is 0.39 μm and D max1 The second active material is mixed with a lithium iron phosphate material with a diameter of 3.69 μm to form a lithium ion battery positive electrode active material in which the mass ratio of the second active material to the first active material is 5:95.
[0073] The other operations are the same as those in Example 1.
[0074] Example 6
[0075] Preparation of positive electrode active material: The average particle size D 50 The minimum particle size is 3.8 μm.min1 The maximum particle size is 1.8 μm. max1 The first active material nickel cobalt manganese oxide material has an average particle size of 8.2 μm and an average particle size of D 50 The minimum particle size is 1.09 μm and D min1 The maximum particle size is 0.82 μm. max1 The second active material is mixed with a lithium iron phosphate material with a diameter of 3.69 μm to form a lithium ion battery positive electrode active material in which the mass ratio of the second active material to the first active material is 20:80.
[0076] The other operations are the same as those in Example 1.
[0077] Example 7
[0078] Preparation of positive electrode active material: The average particle size D 50 The minimum particle size is 3.8 μm and D min1 The maximum particle size is 1.8 μm. max1 The first active material nickel cobalt manganese oxide material has an average particle size of 5.6 μm and an average particle size of D 50 The minimum particle size is 1.09 μm and D min1 The maximum particle size is 0.82 μm. max1 The second active material is mixed with a lithium iron phosphate material with a diameter of 3.69 μm to form a lithium ion battery positive electrode active material in which the mass ratio of the second active material to the first active material is 20:80.
[0079] The other operations are the same as those in Example 1.
[0080] Comparative Example 1
[0081] Preparation of positive electrode active material: The average particle size D 50 The minimum particle size is 3.8 μm and D min1 The maximum particle size is 1.8 μm. max1 The first active material, lithium nickel cobalt manganese oxide material with a particle size of 7.0 μm, is used as the positive electrode active material of the lithium ion battery.
[0082] The other operations are the same as those in Example 1.
[0083] Comparative Example 2
[0084] Preparation of positive electrode active material: The average particle size D 50 The minimum particle size is 3.8 μm and D min1 The maximum particle size is 1.8 μm. max1 The first active material nickel cobalt manganese oxide material has an average particle size of 7.0 μm and an average particle size of D 50 The minimum particle size is 1.09 μm and D min1 The maximum particle size is 0.39 μm and D max1The second active material is mixed with a lithium iron phosphate material with a diameter of 3.69 μm to form a lithium ion battery positive electrode active material in which the mass ratio of the second active material to the first active material is 2:98.
[0085] The other operations are the same as those in Example 1.
[0086] Comparative Example 3
[0087] Preparation of positive electrode active material: The average particle size D 50 The minimum particle size is 3.8 μm and D min1 The maximum particle size is 1.8 μm. max1 The first active material nickel cobalt manganese oxide material has an average particle size of 7.0 μm and an average particle size of D 50 The minimum particle size is 1.09 μm and D min1 The maximum particle size is 0.39 μm and D max1 The second active material is mixed with a lithium iron phosphate material with a diameter of 3.69 μm to form a lithium ion battery positive electrode active material in which the mass ratio of the second active material to the first active material is 26:74.
[0088] The other operations are the same as those in Example 1.
[0089] Comparative Example 4
[0090] Preparation of positive electrode active material: The average particle size D 50 The minimum particle size is 3.8 μm and D min1 The maximum particle size is 4.8 μm. max1 The first active material nickel cobalt manganese oxide material has an average particle size of 7.0 μm and an average particle size of D 50 The minimum particle size is 1.29 μm and D min1 The maximum particle size is 1.03 μm. max1 The second active material is mixed with a lithium iron phosphate material with a diameter of 3.69 μm to form a lithium ion battery positive electrode active material in which the mass ratio of the second active material to the first active material is 5:95.
[0091] The other operations are the same as those in Example 1.
[0092] Comparative Example 5
[0093] Preparation of positive electrode active material: The average particle size D 50 The minimum particle size is 3.8 μm and D min1 The maximum particle size is 1.33 μm. max1 The first active material nickel cobalt manganese oxide material has an average particle size of 15.3 μm and an average particle size of D 50 The minimum particle size is 1.09 μm and D min1 The maximum particle size is 0.39 μm and D max1The second active material is mixed with a lithium iron phosphate material with a diameter of 3.69 μm to form a lithium ion battery positive electrode active material in which the mass ratio of the second active material to the first active material is 5:95.
[0094] The other operations are the same as those in Example 1.
[0095] Comparative Example 6
[0096] Preparation of positive electrode active material: The average particle size D 50 The minimum particle size is 3.8 μm and D min1 The maximum particle size is 1.8 μm. max1 The first active material nickel cobalt manganese oxide material has an average particle size of 17.0 μm and an average particle size of D 50 The minimum particle size is 1.09 μm and D min1 The maximum particle size is 0.39 μm and D max1 The second active material is mixed with a lithium iron phosphate material with a diameter of 3.69 μm to form a lithium ion battery positive electrode active material in which the mass ratio of the second active material to the first active material is 5:95.
[0097] The other operations are the same as those in Example 1.
[0098] The compositions of the positive electrode active materials in Examples 1 to 7 and Comparative Examples 1 to 6 are shown in Table 1.
[0099] Examples 1 to 7 and Comparative Examples 1 to 6 use the above-mentioned preparation method to prepare lithium ion batteries, and their performances are tested. The test results are shown in Table 2.
[0100] Table 1. Composition of positive electrode active materials in Examples 1 to 7 and Comparative Examples 1 to 6
[0101]
[0102] Table 2. Performance of lithium-ion batteries in Examples 1 to 7 and Comparative Examples 1 to 6
[0103]
[0104] Please refer to Table 1 and Table 2. In Examples 1 to 7, the particle size range of the first active material and the second active material is controlled, for example, the ratio of the minimum particle size to the minimum particle size of the first active material is controlled within the range of (1:3) to (1:8), the ratio of the minimum particle size to the minimum particle size of the second active material is controlled within the range of (1:2) to (1:10), and the ratio of the average particle size of the first active material to the second active material is controlled within the range of (3:1) to (15:1). At the same time, the mass ratio of the second active material to the first active material is within 5% to 25%, so that the area of the second active material covering the first active material accounts for 5% to 20% of the area of the first active material, thereby increasing the cycle life of the obtained lithium ion battery to more than 1900 cycles, and the capacity retention rate is greater than 90%. In Comparative Example 1, only the first active material is added as the positive electrode active material, and the cycle life of the obtained lithium ion battery is far inferior to the cycle life of the lithium ion battery in the embodiment. In Comparative Examples 2 and 3, when the mass ratio of the second active material doped with the first active material is too large or too small, and in Comparative Examples 4 to 6, when the minimum particle size of the first active material or the minimum particle size of the second active material is too large or too small, the cycle life and capacity retention rate of the obtained lithium ion battery are reduced. This shows that the small-particle lithium iron phosphate material is coated on the surface of the large-particle nickel cobalt manganese oxide material, and the particle size range and doping ratio of the two materials are controlled, which can effectively prevent the occurrence of side reactions between the nickel cobalt manganese oxide material and the electrolyte, thereby extending the service life of the battery cell and improving the cycle life and rate performance of the lithium ion battery.
[0105] See also Figure 2 and Figure 3 As shown, Figure 2 The figure is a cycle trend diagram of the lithium ion batteries obtained in Examples 1 to 3 and Comparative Example 1. The initial capacity of the lithium ion batteries in Examples 1 to 3 is greater than 97%, and the initial capacity of the lithium ion battery in Comparative Example 1 is less than 95%. And as the number of cycles increases, after the number of cycles is greater than 500, the capacity of the lithium ion batteries in Examples 1 to 3 after cycles is still greater than 95%, while the capacity of the lithium ion battery in Comparative Example 1 after cycles is greatly reduced. Figure 3 The storage performance diagram of the lithium ion batteries obtained in Examples 1 to 3 and Comparative Example 1 is shown. Under the storage condition of 60° C., the recovery capacity of the lithium ion batteries in Examples 1 to 3 within 45 days is greater than 100%, while the recovery capacity of the lithium ion battery in Comparative Example 1 is less than 100%. It is apparent that the cycle performance of the lithium ion battery obtained by the present invention is improved, the service life of the battery cell is extended, and the economic benefits of the lithium ion battery are greatly improved.
[0106] In summary, the present invention proposes a lithium-ion battery and its application, by selecting a first active material and a second active material of different particle sizes, and controlling the particle size ratio of the first active material and the second active material, the first active material and the second active material are mixed in different proportions to prepare a positive electrode active material for a lithium battery. The particles of the two active materials are better filled and fused, so that the second active material is coated on the surface of the first active material with a large particle size, preventing the occurrence of side reactions between the lithium nickel cobalt manganese oxide material and the electrolyte, thereby extending the service life of the battery cell. At the same time, the compaction density and filling density of the pole piece are improved, thereby improving the cycle stability and storage performance of the lithium-ion battery.
[0107] The above description is only a preferred embodiment of the present application and an explanation of the technical principles used. Those skilled in the art should understand that the scope of the invention involved in the present application is not limited to the technical solution formed by a specific combination of the above-mentioned technical features, but should also cover other technical solutions formed by any combination of the above-mentioned technical features or their equivalent features without departing from the inventive concept, such as a technical solution formed by replacing the above-mentioned features with (but not limited to) technical features with similar functions disclosed in this application.
[0108] Except for the technical features described in the specification, the remaining technical features are known technologies to those skilled in the art. In order to highlight the innovative features of the present invention, the remaining technical features will not be described here in detail.
Claims
1. A lithium-ion battery, comprising a positive electrode sheet, a negative electrode sheet and a separator located therebetween, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode active material located on at least one surface thereof, and the negative electrode sheet comprises a negative electrode current collector and a negative electrode active material located on at least one surface thereof, characterized in that: The positive electrode active material comprises at least: a first active substance; and a second active substance, wherein the second active substance is coated on the first active substance; The area of the second active material covering the first active material accounts for 5% to 20% of the area of the first active material, and the average particle size D of the first active material is 50 The average particle size D of the second active material 50 The ratio ranges from (3:1) to (15:1).
2. The lithium-ion battery according to claim 1, characterized in that The mass proportion a of the second active material in the first active material and the second active material and the capacity attenuation coefficient y satisfy the relationship: y=-4×10 -5 x+m1, where 5%≤a≤10%, 0.9646≤m1≤0.9846; y=-3×10 -5 x+m2, where 10%<a≤20%, 0.9718≤m2≤0.9918; y=-3×10 -5 x+m3, where 20%<a≤30%, 0.9787≤m3≤0.9987; Wherein, x is the number of cycles, m1, m2 and m3 are the initial capacity attenuation coefficients of the lithium-ion battery, the capacity attenuation coefficient y is the ratio of the discharge capacity of the xth cycle to the first discharge capacity, and 50≤x≤2000.
3. The lithium-ion battery according to claim 1, characterized in that The mass ratio of the second active material doped with the first active material is 5% to 25%.
4. The lithium-ion battery according to claim 1, characterized in that: The minimum particle size D of the first active substance min1 With the maximum particle size D max1 The ratio ranges from (1:3) to (1:8).
5. The lithium-ion battery according to claim 4, characterized in that: The minimum particle size D of the second active substance min2 With the maximum particle size D max2 The ratio ranges from (1:2) to (1:10).
6. The lithium-ion battery according to claim 1, characterized in that The first active material at least comprises a nickel cobalt manganese oxide lithium material, and the general formula of the nickel cobalt manganese oxide lithium material is LiNi m Co n Mn 1-m-n O2, where 0.1≤m≤0.9, 0<n≤0.
3.
7. The lithium-ion battery according to claim 1, characterized in that: The second active material at least includes a doped lithium iron phosphate material, the general formula of the lithium iron phosphate material is LiFeMPO4, wherein the element M is at least one of Mn, Ti, Zr, Al, Sn, Zn, Mg, Cu, In, Ga or Ta.
8. The lithium-ion battery according to claim 1, characterized in that The recovery capacity of the lithium-ion battery within 45 days is greater than 100%.
9. The lithium-ion battery according to claim 1, characterized in that: The surface density of the positive electrode sheet is 1.4 to 3 times that of the negative electrode sheet.
10. An electrochemical device, characterized in that: The invention comprises a lithium ion battery as claimed in any one of claims 1 to 9.
Citation Information
Cited By
Positive electrode material, positive electrode plate, electrochemical device and preparation method of positive electrode material
CN119864386A